Role of Paracoccidioides brasiliensis cell wall fraction containing β-glucan in tumor necrosis factor-alpha production by human monocytes: Correlation with fungicidal activity - Anjos, A. R. [UNESP] (2002)
The polysaccharide fraction of Paracoccidioides brasiliensis mycelial cell wall (F1 fraction), the active component of which is composed of β-glucan, was investigated in regard to the activation of human monocytes for fungal killing. The cells were primed with interferon-γ (IFN-γ) or F1 (100 and 200 μg ml-1) or F1 (100 and 200 μg ml-1) plus IFN-γ for 24 h and then evaluated for H2O2release. In other experiments, the cells were pretreated with the same stimuli, challenged with a virulent strain of P. brasiliensis and evaluated for fungicidal activity and levels of tumor necrosis factor (TNF-α) in the supernatants. F1 increased the levels of H2O2in a similar manner to IFN-γ. However, a synergistic effect between these two activators was not detected. On the contrary, a significant fungicidal activity was only obtained after priming with IFN-γ plus F1. This higher activity was associated with high levels of TNF-α in the supernatants of the cocultures. Overall, P. brasiliensis F1 fraction induced human monocytes to release relatively high levels of TNF-α, which, in combination with IFN-γ, is responsible for the activation of human monocytes for effective killing of P. brasiliensis.